The Correlation between Pre-service EFL Teachers’ Extroversion and English Speaking Skills - Heriyanti Tahang; Anthoneta Mirino; Taslim Taslim; Isnaeni Wahab; Sitti Aisyah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This study examines the relationship between extroversion and speaking proficiency among 27 pre-service English teachers at Universitas Muhammadiyah Sorong. Using a correlational research design, data were collected through the Revised-Short Form Eysenck Personality Questionnaire (EPQR-S) and a speaking skills test using a rubric by O'Malley (1996). The data were analysed using SPSS version 27 and Pearson product-moment correlation techniques. The results reveal an insignificant negative correlation (r = -0.108, p > 0.05) between extroversion and speaking skills, indicating no substantial link between these variables. Most students displayed moderate extroversion, but their speaking scores predominantly fell into the